2016
DOI: 10.1177/1479972316642367
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk, chronic obstructive pulmonary disease and pulmonary rehabilitation

Abstract: Patients with chronic obstructive pulmonary disease (COPD) who participate in pulmonary rehabilitation (PR) often have concomitant cardiovascular disease (CVD), which is a frequently undiagnosed and undertreated comorbidity. CVD contributes to the burden of the disease and is associated with an increased risk for hospitalizations and mortality. Optimizing the diagnosis and management of cardiovascular risk and disease should be considered as part of the holistic approach of PR. In addition, we need to consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Aside from pharmacological strategies, pulmonary rehabilitation (PR) is recommended for patients with COPD as part of integrated patient management [1]. For those with CVD, it is important to consider both diseases when creating PR programmes [150]. Retrospective analyses and prospective studies provide conflicting insight into the effect of CVD on PR efficacy, with the former suggesting a reduction in the ability to achieve a clinically-important difference in 6-minute walking distance and health status in patients with metabolic diseases versus those without [151].…”
Section: Muscarinic Antagonistsmentioning
confidence: 99%
“…Aside from pharmacological strategies, pulmonary rehabilitation (PR) is recommended for patients with COPD as part of integrated patient management [1]. For those with CVD, it is important to consider both diseases when creating PR programmes [150]. Retrospective analyses and prospective studies provide conflicting insight into the effect of CVD on PR efficacy, with the former suggesting a reduction in the ability to achieve a clinically-important difference in 6-minute walking distance and health status in patients with metabolic diseases versus those without [151].…”
Section: Muscarinic Antagonistsmentioning
confidence: 99%
“…Kardiovaskuläre Erkrankungen (wie arterielle Hypertonie, koronare Herzkrankheit, kongestive Herzinsuffizienz, periphere Gefäßerkrankungen und pulmonale Hypertonie) gehören zu den Komorbiditäten mit der höchsten Prävalenz und den stärksten Auswirkungen bei Patienten mit COPD (13%–68% der Bevölkerung), Asthma (3%–25% der Bevölkerung) und ILD (8%–86% der Bevölkerung) [6-13]. Sie verschlechtern den funktionellen Status und die gesundheitsbezogene Lebensqualität der Patienten noch weiter, erhöhen das Hospitalisierungs- und Mortalitätsrisiko (Hazard Ratio (HR) 1,1–3,4 [14-17]) und tragen so zu einer erhöhten wirtschaftlichen und gesellschaftlichen Belastung sowie zu einer Verschlechterung der Prognose bei [7, 9, 10, 12]. Daher sollte bei der Behandlung dieser Patienten der Blick über die Lunge hinaus gehen [18] und eine umfassende Beurteilung sowie Behandlung der kardiovaskulären Komorbiditäten mit maßgeschneiderten Interventionen wurde empfohlen [7, 12, 19, 20].…”
Section: Hintergrundunclassified
“…58,59 Many review articles have suggested this is an area of future research. [60][61][62] Skeletal muscle dysfunction is well recognised in COPD and CHF 10 and is a frequently reported measure in PR studies, although less commonly in CHF rehabilitation studies. Interestingly, the measurement Health-related quality of life Largely generic questionnaire, such as the potential use of the EuroQol 5D-3L, 26 EuroQol 5D-5L, 27 World Health Organisation quality of life (WHOQOL)-100 28,29 or WHOQOL-BREF 30…”
Section: Summary Of Main Findingsmentioning
confidence: 99%